2005
DOI: 10.1002/bit.20688
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological performance of a novel block copolymer nerve guide

Abstract: Although the ability to regenerate is evident in the nervous system, lesioned neurites are unable to cross gaps in neuronal pathways. In order to bridge gaps, guiding cues are essential to direct neurite regrowth. To overcome many of the shortcomings of polymer-based nerve guides, we developed a bioresorbable nerve guide composed of a novel trimethylene carbonate-caprolacton block copolymer (TMC-CL). Pore formation was controlled by using special solvent/precipitation media compositions in combination with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…SCs enhance axonal growth in vitro by one order of magnitude [27], support spinal cord repair [18] and regeneration via PNS implants [51]. In a most recent approach, we have found that poly-(TMC-CL) nerve guides support regeneration of severed rat median nerves [52] and the spinal cord [21] only if nerve guides have been pre-filled with SCs. Thus, SCs have become a preferred candidate for biohybrid implants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCs enhance axonal growth in vitro by one order of magnitude [27], support spinal cord repair [18] and regeneration via PNS implants [51]. In a most recent approach, we have found that poly-(TMC-CL) nerve guides support regeneration of severed rat median nerves [52] and the spinal cord [21] only if nerve guides have been pre-filled with SCs. Thus, SCs have become a preferred candidate for biohybrid implants.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases a drop of poly-lactide solution was employed for additional fixation. The needle allowed to easily insert all PGA filaments into a resorbable, semipermeable nerve guide conduit made of poly-trimethylene carbonate-e-caprolactone (TMC-CL) [21]. The inner diameter of the conduit was approximately 1 mm, and the thickness of the conduit wall was 100 mm.…”
Section: Polymer and Silicon Structuresmentioning
confidence: 99%
“…Current investigation is focusing on developing conduits that can actively enhance the migration of Schwann cells and axons during regeneration or that could stimulate regeneration over longer nerve gap lengths. 31,32 Over the past several years, there has been increased interest in decellularized nerve allografts. 33,34 Allografts may ultimately prove to be best: the convenience of an alloplast with the effectiveness of an autograft.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel ® contains a number of ECM molecules and growth factors and has been used as filler for nerve guidance channels of biodegradable [137,154,155] or non-biodegradable source [66,78] and cell-encapsulating device [92] (Table 3F). Although it had superior properties in promoting neurite growth and enhancing cell survival, proliferation and functioning, Matrigel ® derivation from a sarcoma cell line source has greatly limited its potential clinical use [11].…”
Section: Cell-carriers With Biodegradable Materialsmentioning
confidence: 99%